Ripensando all’opera fotografica di Claude Cahun a partire da fonti e contesti - Sorrentino, Cristiana (Rivista di studi di fotografia. Journal of Studies in Photography, 2018)
This article aims to reflect on the methodological questions raised by the historiography on Claude Cahun’s work in the past two decades. Often considered as pure images rather than objects, her photographs have been scrutinized mostly from an interpretive and iconological perspective, with little interest in their factual meaning. Building upon this premise, the essay offers to reconsider the biographical and socio-cultural origins of some of Cahun’s photographs, with particular attention to issues of philology and contextualization.